Sustainable heritage: Analytical study on the viability of adaptive reuse with social approach, case study of Asia Heritage Row, Kuala Lumpur - Abdullah, Fadzidah; Basha, Brunilda; Raza, Ali (American Scientific Publishers, 2017)
Historic buildings maintain the local characteristics and preserve the culture and history of a country. This historical and cultural significances as a legacy can be passed to next generation by conserving the historical buildings. Nowadays in the process of conservation, Adaptive Reuse Practice has been necessary, especially when historical buildings are no longer functioning its original purpose. Moreover, adaptive reuse holds different dimensions of sustainability that of economic, environmental and social. In the pursuit of the sustainable development, social sustainability has been the new parameter to investigate the viability of adaptive reuse. In this regard an attempt has been made as a main objective to investigate the viability of adaptive reuse and its social sustainability. Asia Heritage Row located in Doraisami Street and Jalan Yap Ah Shak, Kuala Lumpur is used for the hypothesis testing. The variables that are measured as parameters in achieving social sustainability are categorized into cultural, aesthetical, social and human comfort. The data is mainly collected from literature review, case study and questionnaires distributed to the users of the case study area. The data is analyzed by determining the statically reliable relationship between adaptive reuse and social sustainability parameters. The associations between variables are examined by correlation. The result show’s that adaptive reuse of Asia Heritage Row Building not only have a social value but preserves the heritage significances as a place of social interaction and also ensures its sustainability. Hope this study would be worthwhile for those who are intending to know or carry out research about the socio-sustainability of readapted heritage buildings in future.